Climate forcing of summer carbon drawdown in the subpolar North Atlantic - Svanevik, Magni (The University of Bergen, 2015)
This thesis present a 9-year long time series of surface seawater fCO2 data obtained aboard the MV Nuka Arctica. The Nuka Arctica provide full seasonal fCO2 measurements which give a good picture of the fCO2 variability between Denmark and Greenland. The ultimate aim is to identify climate forcing of summertime fCO2 variations as observed from the Nuka data. The observed variations in interannual summertime fCO2 result from both physical and biological processes. To separate these effects, fCO2 was normalised to a constant temperature and to a reference year. This leaves fCO2 variations caused only by biology and mixing, the main drivers behind summertime fCO2. The oceanic drivers, represented by chlorophyll-a and MLD data, were used to detect and determine the strength of the biological activity (the primary production). Environmental parameters were applied to identify climate forcing of the oceanic drivers and ultimately the fCO2. Temperature were found to have the strongest effect on May MLD, which determined the timing of the primary production and fCO2 drawdown. In the summer months a combination of wind and temperature governed the MLD and stratification, which ultimately determined the strength of the fCO2 drawdown. Master i Meteorologi og oseanografi MAMN-GEOF GEOF399